1983
DOI: 10.1128/iai.40.3.1192-1197.1983
|View full text |Cite
|
Sign up to set email alerts
|

Mouse hepatitis virus type 4 infection of primary glial cultures from genetically susceptible and resistant mice

Abstract: Mouse hepatitis virus type 4 infection of primary glial cultures, which consisted principally of astrocytes (marked by glial fibrillary acidic protein) from encephalitis-susceptible BALB/c or F1 (BALB/c x SJL/J) hybrid mice and resistant SJL/J mice, was studied. Primary neuron cultures from BALB/c and F1 hybrid mice were previously shown to be permissive and were destroyed within 5 days by infection with mouse hepatitis virus type 4, whereas neurons from SJL/J mice were fully resistant. In contrast, in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…The uniqueness of differential tropisms of CV in the rat CNS appears to be species specific, as indicated by comparison of results on rat and murine cells. In the latter, JHMV can replicate equally well in astrocytes, neurons (Knobler et al, 1981a, b;Dubois-Dalcq et al, 1982;Collins et al, 1983), and oligodendrocytes (unpublished results). The in vitro infectability of rat neurons remains to be demonstrated, although infection of these cells within the CNS has been documented (Nagashima et CAL, 1978;Sorensen et al, 1984).…”
Section: Discussionmentioning
confidence: 84%
“…The uniqueness of differential tropisms of CV in the rat CNS appears to be species specific, as indicated by comparison of results on rat and murine cells. In the latter, JHMV can replicate equally well in astrocytes, neurons (Knobler et al, 1981a, b;Dubois-Dalcq et al, 1982;Collins et al, 1983), and oligodendrocytes (unpublished results). The in vitro infectability of rat neurons remains to be demonstrated, although infection of these cells within the CNS has been documented (Nagashima et CAL, 1978;Sorensen et al, 1984).…”
Section: Discussionmentioning
confidence: 84%
“…These observation are consistent with published reports showing that M HV-J H M has a tropism for astrocytes in dissociated mouse spinal cord cultures,"" 15 and that MHV-JHM may persist for long periods of time in primary cultures of mouse or Lewis rat astrocytes .' o, 15 The majority of MHV-JHM infected cells in the CNS were not further identified in this study . It remains important to identify what other types of CNS cells are infected in both symptomatic and asymptomatic mice, but our attempts to do so using cellspecific markers for neurons and oligodendrocytes 16-20 have been unsuccessful thus far .…”
Section: Symptomatic Mice Born To Immunized Damsmentioning
confidence: 83%
“…It should be kept in mind that the infectability of oligodendrocytes by these agents cannot account entirely for the CNS diseases observed, since the ability of coronaviruses to replicate in neurons and other cell types has been abundantly documented (Nagashima et aL, 1978;Knobler et aL, 1981aKnobler et aL, , 1981bDubois-Dalcq et aL, 1982;Collins et aL, 1983;Sorensen et aL, 1984;Beushausen and Dales, 1985). Our recent investigations using cDNA probes have, in fact, shown by in situ hybridization that latent JHMV can be maintained for prolonged periods in the cytoplasm of neurons within specific areas of the rat brain, particularly in the hippocampus (Sorensen and Dales, 1985), suggesting that neurons may function as repositories of latent and persistent infections.…”
Section: Discussionmentioning
confidence: 99%
“…1981b; Dubois-Dalcq et al, 1982;Collins et In studying the factors involved in the al ., 1983). Concerning oligodendrocytes of development of demyelinating diseases it rodents, which have been implicated as the has been demonstrated that several strains in viva targets, those from the rat are inof murine coronaviruses including MHV-deed infectable in vitro by JHMV (Beus-A59 (Lavi et ak, 1984), MHV3 (Hirano et aL, hausen and Dales, 1985).…”
Section: Introductionmentioning
confidence: 99%